Innovation as a practice: Why automation will not kill innovation - Redín, Dulce M.; Cabaleiro-Cerviño, Goretti; Rodriguez-Carreño, Ignacio; Scalzo, German (Frontiers in Psychology, 2023)
In the wake of the contemporary culture of continuous innovation and ‘change before you have to’, innovation has been identified with economic gains rather than with creating added value for society. At the same time, given the current trends regarding the automation of business models, it seems that workers are destined to be replaced by machines in the labor market. In this context, we attempt to explore whether current robots and Artificial Intelligence (AI) will be able to innovate, and to what extent it is an activity inherent to human nature. Following the need for a more anthropological view of innovation, we make use of MacIntyrean categories to present innovation as a domain-relative practice with creativity and practical wisdom as its corresponding virtues. We explain why innovation can only be understood within a tradition as it implies participating in the inquiry regarding the principle and end of practical life. We conclude that machines and ‘intelligent’ devices do not have the capacity to innovate and they never will. They may replicate the human capacity of creativity but they do not have the necessary conditions to be a locus of virtue or engage with a tradition.